2010
DOI: 10.1111/j.1478-4408.2010.00271.x
|View full text |Cite
|
Sign up to set email alerts
|

Photorealistic ink‐jet digital printing – factors influencing image quality, image stability and print durability

Abstract: Digital cameras have now replaced film-based cameras as the most popular method of still image capture. As a consequence, there has been a rise in growth of the photo-realistic digital-printer market as many amateur and professional photographers choose to produce their own hard copy images. The most popular digital printing technology for producing photo-realistic images is currently drop-ondemand ink jet. There has been much research into key factors influencing the quality, stability and durability of image… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 31 publications
(28 reference statements)
0
6
0
Order By: Relevance
“…It primarily involves pigment, resin and process acceleration additives. When combined or shaken by a triboelectric impact, the toner particles become electrically charged [6]. The composition of the toner contributes not only to its imaging properties but also to maintaining and controlling charging properties.…”
Section: Figure 1 Digital Printing Schemementioning
confidence: 99%
“…It primarily involves pigment, resin and process acceleration additives. When combined or shaken by a triboelectric impact, the toner particles become electrically charged [6]. The composition of the toner contributes not only to its imaging properties but also to maintaining and controlling charging properties.…”
Section: Figure 1 Digital Printing Schemementioning
confidence: 99%
“…This means that better compatibility of the resin maintains a stable ink-water balance on the printing press. Kazlauciunas 15 showed that the compatibility of the ink components improved the ink stability. Figure 2 shows the changes in the elastic modulus and viscous modulus of inks with varying shear stress.…”
Section: Role Of Resin Molecular Weightmentioning
confidence: 99%
“…CI Direct Blue 199. Other dyes that have been previously used are well documented [47][48][49][50], as are other currently used dyes [43,51].…”
Section: Hard-copy Non-impact Digital Printingmentioning
confidence: 99%
“…CI Pigment Blue 15:3, CI Pigment Red 122, CI Pigment Yellow 74, CI Pigment Violet 19, and CI Pigment Black 7. Other pigments that are currently used, and others that are being actively promoted, have been documented .…”
Section: Hard‐copy Non‐impact Digital Printingmentioning
confidence: 99%